Expression of MUC5AC in normal gastric mucosa, intestinal metaplasia and gastric carcinoma by immunohistochemistry - Bhat, Shuaeb; Bashir, Nusrat; Mir, Showkat Ahmad (International Journal of Research in Medical Sciences, 2019)
Background: Carcinomas of the stomach are a heterogeneous group of lesions in terms of architecture, pattern of growth, cell differentiation, and histogenesis. Altered MUC5AC expression patterns have been reported previously in intestinal metaplasia as well as in gastric cancer. The aim of the study was to analyse the expression pattern of MUC5AC in normal, pre-neoplastic and neoplastic gastric epithelium. Methods: Formalin fixed paraffin embedded sections of sixty cases which include twenty cases of each normal gastric mucosa, intestinal metaplasia and gastric carcinoma were taken up for the study and subjected to immunohistochemistry using MUC5AC. Results: The intensity of MUC5AC immunostaining in normal gastric mucosa, intestinal metaplasia and gastric carcinoma was evaluated. Immunoreactivity was graded as 0 (negative), ± (trace positive), + (positive) or ++ (strongly positive). Statistical analysis was performed with Chi-Square test and significant differences were noted between these 3 groups (p value <0.05). Conclusions: Authors concluded that MUC5AC expression rates might be good parameters in progression of intestinal metaplasia to gastric carcinoma and might be a good prognostic marker for gastric carcinoma as it is very well implicated in understanding of gastric carcinogenesis.